Ibrahim, Son of Mahmoudek: Accession to Power and Purses (2) » - A.L. Ponomarev (Золотоордынское обозрение)
The death of the Crimean khan Haij Garey on 25 August 1466 was followed by two months of the political turmoil. Sons of the late ruler, Mengli Garey and Nur Dawlat, were two pretenders well-known to the historians. But numismatic material and newly found archival documents prove that there was one more claimant khan. He was the protege of the Shirin bek Mamak and the copper puls of Caffa with the forked tamga testify that the Genoeses were inclined to accept his supremacy. The said heraldic symbol didn’t belong to Garey khans and it was never more used for the coins of Caffa or the khanate after 1441, when Tartar beks elected Haji Garey to be their lord. These puls were the fractional currency that became necessary after there had happened the monetary reform in the khanate and those old silver dangs started to circulate side by side with a new silver denomination – aqcha. The author has discovered that these puls have die links with aqcha coins of Nur Dawlat and moreover he has found that the third «Emperor» had been mentioned in the unpublished accounts of the Genoese treasury, composed in September and October 1466. The shape of his tamga as well the steady political predilections of the Shirin beks demonstrate his kinship with Ulugh Muhammad. The name of this previously unbeknown Crimean khan, who became next year the khan of the Kazan khanate, was Ibrahim. The name of this khan is written on those coins which were earlier attributed to the Siberian khan Ibrahim (Ibak) without real, only on far-fetched and untutored grounds.